Comparative legal studies in agricultural law - Budzinowski, Roman (Przegląd Prawa Rolnego, 2024)
The purpose of writing this article was to formulate a general reflection on comparative legal studies in agricultural law. The considerations carried out confirm the peculiarity of comparative research in this field of law, as well as the evolution of its subject matter. At the dawn of agricultural law, comparative legal studies referred to the entire branch of agricultural law, although their character was rather that of ‘approximating’ its shape and development in particular legal orders. In the course of time, the comparison became focused on legal institutions, and nowadays on agricultural law as a branch of law. The search for answers addressing contemporary challenges facing agriculture and agricultural law has further expanded the subject of comparison, although today it is viewed from the perspective of a research problem, often of a global nature, rather than from the perspective of individual legal systems and institutions contained in them. The considerations presented here also justify the claim that Polish agricultural lawyers may be proud of their successes in conducting comparative legal research in agricultural law, and that the subject and results of such their research are comparable to the achievements of the Western European science. At their core are considerations of Aleksander Lichorowicz who almost 40 years ago substantiated the need for this kind of research in agricultural law.